Adapting Businesses to the 6G Security Paradigm: Insights from Commerce 5.0 - Amin, Ruhul; Goda, Dileep Reddy; Ande, Janaki Rama Phanendra Kumar (Asian Business Review, 2024)
Within the context of Commerce 5.0, this study examines organizations' potential and difficulties when adjusting to the 6G security paradigm. The primary goals are to look into how 6G technology is developing, assess cybersecurity opportunities and problems, pinpoint strategic imperatives for business adaptation, investigate using Commerce 5.0 to gain a competitive edge, and look at upcoming trends and things business leaders should know. The approach used is a thorough analysis of the knowledge and insights from Commerce 5.0. Key findings point to the revolutionary potential of 6G technology for enterprises, new cybersecurity requirements, and strategic imperatives. The report emphasizes the significance of valuing ethics and cybersecurity readiness and embracing hyperconnectivity, customization, and innovation. The consequences of policy point to the need for infrastructure spending, cybersecurity best practices promotion, encouragement of innovation and teamwork, and the creation of regulatory frameworks for new technology. This study offers insightful information to industry stakeholders, legislators, and corporate executives trying to make sense of the intricacies of the 6G security paradigm while promoting innovation and expansion in the digital economy.
Keywords: 6G Security; Business Adaptation; Commerce 5.0; Security Paradigm; Cybersecurity Trends; Next-Generation Networks; Future Business Landscape